Multivariate analyses to establish reference values for soils in Médio Paraíba, state of Rio de Janeiro, Brazil (Revista Ciência Agronômica, 2023)
Quality Reference Values (QRVs) for potentially toxic elements are obtained from background levels in soils.However, this determination from mean values or percentiles is not appropriate given the variability in the natural distributionof these elements in soils. Therefore, the objective of this study was to propose a new methodology to establish the QRVs,using the Médio Paraíba region (RJ, Brazil) as an example, from groups of soils defined based on the pseudo-total levels ofB, Ba, Co, Cr, Cu, Ni, Pb, and Zn through the use of multivariate analyses and discriminant functions. A total of 40 points,collected at depths of 0-20 and 20-40 cm, were used for the determination of pseudo-total contents, according to the EPA 3051Amethodology. The samples were separated into three groups to better represent the variability of the soils of the region. Theclassification functions were obtained based on the variables Mn, Fe, and Mg. In general, the groups G1 and G2 presented lowervalues than the ones obtained when the sample universe was used, whereas G3 presented higher values. The QRVs obtainedfrom the soil groups presented substantial differences that translate into advantages for the management of the contaminatedareas of the region.